Changes in Enzymatic Activity of Fish and Slaughter Animals Meat after High Pressure Treatment at Subzero Temperatures - Malinowska-Pańczyk Edyta; Kołodziejska Ilona (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine changes in the activity of proteolytic enzymes and transglutaminase of fish and mammal meat after pressurization at subzero temperatures. The activity was measured at the optimal pHs determined for enzymes from particular types of tested meat. It was found that increasing the pressure in the range of 60-193 MPa, did not change significantly the activity of acidic proteases of cod flesh, while the activity of neutral and alkaline proteases decreased drastically. Proteolytic enzymes from salmon flesh were more resistant than those from cod flesh. They maintained or increased (neutral protease) activity after pressurization. The activity of the endogenous enzymes of bovine meat increased with pressure increase, except for acidic proteases, the activity of which was reduced after treatment at 193 MPa to the level similar to unpressurized meat. Endogenous proteases of porcine meat were activated by high-pressure treatment. It has been shown that activity of TGase in unpressurized flesh from cod was 5 times higher than that from unpressurized salmon. Depending on the type of meat, these enzymes were also significantly different in their sensitivity to pressure. The pressure of 60 and 193 MPa led to a complete inactivation of the TGase in cod flesh, while the activity of salmon flesh TGase was decreased only by 15 and 21%, respectively.